Deciphering the cooling history of the garzon massif: a body that records variable exhumation patterns? - Leidy Carolina Sandoval-Espinel; Mauricio Alberto Bermúdez; John Jairo Sandoval Espinel (Brazilian Journal of Geology)
Abstract The Northern Andes in Colombia are involved in a continuous mountain-building process along an active subduction zone, resulting in significant Cenozoic compression, leading to substantial Neogene shortening and topographic development. It is believed that, during the Miocene, some major geological structures reached their present-day elevation; this is the case of the Garzón Massif, an orographic barrier between the Middle Magdalena Valley and the Putumayo Basins. Some studies have been performed in order to understand the exhumation history of the Massif; however, whether the cooling process was slow or fast, and whether this occurs continuously or episodically, as well as the possible influence of faults on exhumation, is a matter of discussion. Using new apatite fission track thermochronology in combination with published data, we aimed to reconstruct the cooling history of the Massif. Our results show that cooling was asynchronous, with fault-bounded blocks cooling independently starting around 70 Ma. Cooling of the southernmost block (B6) occurs during Maastrichtian (~4.9°C/Myr), in blocks B2, B3, and B5 in Eocene (~5.3–5.6°C/Myr), and in blocks B1 and B5 from Late Oligocene to Miocene (~9°C/Myr and ~23°C/Myr, respectively). Faster cooling rates from the Miocene onward may be related to the accretion of the Panama-Choco block against the continent.